Evaluation as antioxidant agents of 1,2,4-triazole derivatives: effects of essential functional groups - Ahmet Cetin, Ibrahim Halil Geçibesler (Journal of Applied Pharmaceutical Science, 2015)
A series of 1,2,4-triazole derivative compounds substituted with groups of phenol and pyridine were synthesized in high yields and screened against several antioxidant activity parameters such as DPPH, ABTS, metal chelating, reducing power and the total antioxidant activity. The compounds showed better than expected antioxidant activity between the studied biological activity parameters. Among these, compound G(2-(5-mercapto-4H-1,2,4-triazol-3-yl)phenol) had a high total antioxidant activity potential with value of 232.12±6.89 mmol/ml. Also showed fairly good ABTS cation radical and DPPH radical scavenging activity with values of IC50 = 4.59±4.19 and IC50 = 7.12±2.32µg/mL respectively. Further, the antioxidant potential of heterocyclic compounds that 1,2,4-triazole derivatives containing different functional groups were compared with various tests performed and has been shown to increase the activity of electron donating groups. Therefore, the present study demonstrates that phenol and pyridine substituted 1,2,4-triazole compounds would be a better prospective in the development of antioxidant agent.
Keywords: 1,2,4-triazole, antioxidant activity, 2-(5-mercapto-4H-1,2,4-triazol-3-yl), phenol.